PERAN END CHILD PROSTITUTIONS AND TRAFFICKING (ECPAT) DALAM MENANGANI EKSPLOITASI SEKSUAL KOMERSIAL ANAK DI THAILAND TAHUN 2016-2019 - Rhimadani, Annisa Mawaddah; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Commercial sexual exploitation of children still frequently occurs in the world, particularly in Thailand. The extremely high level of vulnerability has drawn the attention of international organizations to take preventive measures. One international organization actively addressing the issue of child sexual exploitation is End Child Prostitution and Trafficking (ECPAT). This study elaborates on the important role of ECPAT in dealing with issues related to child exploitation practices. This research utilizes Civil Society Organization (CSO) theory to analyze the role of ECPAT in addressing the issue of Commercial Sexual Exploitation of Children (CSEC) in Thailand. The research method used is qualitative with an analytical descriptive model. Secondary data is obtained through a literature review from various sources, including books, academic journals, official websites, and annual reports from relevant organizations. ECPAT plays three key roles in preventing child sexual exploitation in Thailand. First, as an educator, ECPAT provides education on the dangers of sexual exploitation in schools. Second, as an agenda setter, ECPAT researches new trends and designs preventive policies. Third, as a counterpart, ECPAT collaborates with private institutions, NGOs, INGOs, and the government to strengthen efforts in the prevention and handling of CSEC cases. This study demonstrates that ECPAT has effectively implemented its programs despite facing significant challenges. With strong commitment, ECPAT has played a crucial role in reducing the incidence of commercial sexual exploitation of children in Thailand in 2019. Keywords: ECPAT, Commercial Sexual Exploitation of Children (CSEC), Thailand, Civil Society Organization (CSO)